Validation and genomic interrogation of the MET variant rs11762213 as a predictor of adverse outcomes in clear cell renal cell carcinoma. Issue 3 (27th October 2015) - Hakimi, A. Ari; Ostrovnaya, Irina; Jacobsen, Anders; Susztak, Katalin; Coleman, Jonathan A.; Russo, Paul; Winer, Andrew G.; Mano, Roy; Sankin, Alexander I.; Motzer, Robert J.; Voss, Martin H.; Offit, Kenneth; et al.
Abstract : BACKGROUND: The exonic single‐nucleotide variant rs11762213 located in the MET oncogene has recently been identified as a prognostic marker in clear cell renal cell carcinoma (ccRCC). This finding was validated with The Cancer Genome Atlas (TCGA) cohort, and the biologic implications were explored. METHODS: The genotype status for rs11762213 was available for 272 patients. Paired tumor‐normal data, genomic data, and clinical information were acquired from ccRCC TCGA data sets. Cancer‐specific survival (CSS) was analyzed with the competing risk method, and Cox proportional hazards regression was used for the analysis of the time to recurrence (TTR). Multivariate competing risk models were fitted to adjust for the validated Mayo Clinic Stage, Size, Grade, and Necrosis (SSIGN) score. RESULTS: The variant allele of rs11762213 was detected in 10.3% of the cohort. After adjustments for the SSIGN score, the risk allele remained a significant predictor for adverse CSS (hazard ratio [HR], 3.88; 95% confidence interval [CI], 1.99‐7.56; P < .0001) and for TTR (OR, 2.97; 95% CI, 1.43‐6.2; P = .003). The mapping of rs11762213 to regulatory regions within the genome suggested that it might affect a DNA enhancer region. RNA and protein sequencing data for MET did not reveal differences in steady‐state expression with stratification by risk allele. CONCLUSIONS: The exonic MET variant rs11762213 is an independent predictor of adverse CSS and TTR in ccRCC and should be integrated into clinical practice for prognostic stratification. Genomic analysis suggests that the single‐nucleotide polymorphism may affect an enhancer region located in the coding region of MET . Further biological mechanistic interrogation is currently underway. Cancer 2016;122:402–410. © 2015 American Cancer Society . Abstract : Using The Cancer Genome Atlas data set, this study validates the idea that the MET germline variant rs11762213 predicts worse cancer‐specific survival and recurrence‐free survival for patients with clear cell renal cell carcinoma. This variant overcomes many of the inherent challenges of biomarker development with respect to intratumoral heterogeneity and can serve as a liquid biopsy for observation strategies in small renal masses.